Fracture behaviour of friction stir welded dissimilar aluminium alloys. (2021) - Khan, Noor Zaman; Maqbool, Annayath; Ahmad, Tariq; Siddiquee, Arshad Noor; Khan, Zahid A.
Abstract: High strength aerospace grade aluminium alloys are considered difficult to be welded by conventional fusion welding processes but Friction stir welding (FSW) process can effectively join these alloys with good joint properties. FSW is being widely used in aircraft construction and tank of space shuttles. After successful joining of Aluminium alloys by FSW, the fracture behavior of the joint need to be investigated for analyzing the joint fracture. In the present paper, dissimilar aluminium alloys were welded successfully at a rotational speed of 710 rpm, traverse speed of 160 mm/min and tool shoulder diameter of 12 mm. The welded joint was tested on tensile testing machine and the fracture location was found to be at heat affected zone (HAZ) of advancing side. HAZ was found to be the weakest portion of the joint due to thermal softening which resulted in grain growth and large-sized coagulated precipitates. Cracking of large-sized coagulated Al2 Cu precipitates resulted in the fracture of the welded joint.